الآثار الواردة عن عمر بن الخطاب في الربا، دراسة تحليلية في المعاملات التجارية المعاصرة - Kabiru Goje; Samer Najeh Abdullah Samarh (Universiti Sains Islam Malaysia, 2024)
This research focuses on the statements of ‘Umar ibn al-Khattab (RDA) on usury and exposes its relationship with the contemporary economy. It defines usury with its categories, selects some Prophetic traditions related to it from several books of Hadith, the book of its commentaries and books of Islamic Jurisprudence (both early and contemporary). The Prophetic traditions that being collected were arranged by themes then analyzed their status of authenticity and weakness by carrying the principle of analyzation of hadith from the scholars. This research also tried to educe from the statement jurisprudential ruling then relates it with the current developments in commercial transactions akin to usury. The researcher concludes on identifying the jurisprudential leanings of ‘Umar (RDA) in the issues of Usury, stating that majority of his choices and leanings is accepted by many companions and Islamic scholars, and that ‘Umar (RDA), during his reign, explained practically how the Islamic Law could encapsulate all the new developments and occurrences of every age with all the evolving legal decisions on all aspects of life.